2021
DOI: 10.1371/journal.pone.0255461
|View full text |Cite
|
Sign up to set email alerts
|

Socio-spatial relations observed in the global city network of firms

Abstract: One of the prevailing approaches to the study of the global economy is the analysis of global city networks based on the activities of multinational firms. Research in this vein generally conceptualises cities as nodes, and the intra-firm relations between them as ties, forming the building blocks for globally scaled interurban networks. While such an approach has provided a valuable heuristic for understanding how cities are globally connected, and how the global economy can be conceived of as a network of ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 97 publications
(110 reference statements)
1
2
0
1
Order By: Relevance
“…North American, European and East Asian cities form three central clusters. These observations corroborate the findings of previous studies that observed a high regional cohesion due to cultural, spatial and linguistic proximity (Rozenblat et al., 2017; Sigler, Martinus, & Loginova, 2021).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…North American, European and East Asian cities form three central clusters. These observations corroborate the findings of previous studies that observed a high regional cohesion due to cultural, spatial and linguistic proximity (Rozenblat et al., 2017; Sigler, Martinus, & Loginova, 2021).…”
Section: Resultssupporting
confidence: 92%
“…Research into city–state relations has a long and diverse history, with a range of scholars emphasizing the crucial role of the state scale in understanding unfolding transformations in the global economy and urban‐scale transformations within and through which they occur (Brenner, 1998). Given the clear connection between cities’ global positionalities and the role(s) of the state in shaping these (Hill & Fujita, 1995; Loginova et al., 2020), a ripe opportunity exists to investigate specifically how global connectivity in cities links back to urban systems, especially when considering the different patterns of socio‐spatial embeddedness generated by the multipolar organization of urban networks in regional and national systems (Derudder et al., 2003a; Rozenblat et al., 2017; Sigler, Martinus, & Loginova, 2021).…”
Section: The Global Scale: From Core World Regions To World City Networkmentioning
confidence: 99%
“…O processo de formação urbana decorre da evolução das atividades humanas e suas influências no território, principalmente frente aos relacionamentos entre estruturas espaciais e sociais, fundamentais à compreensão, em várias áreas de conhecimento, das próprias interações político-econômicas (Sigler;Martinus;Loginova, 2021). Dietzsch (2006, p.727) argumenta que a cidade pode ser "focalizada como um modo de existência da sociedade, como um espaço polifônico e em suas relações com a educação".…”
Section: Considerações Iniciaisunclassified
“…The variegated investment activities of corporations are an important component of the real economic world [1][2][3]. Demystifying the processes of corporate diversified strategies and investment behaviors will contribute to our understanding of the driving forces behind the operation and evolution of the socioeconomic system [4][5][6].…”
Section: Introductionmentioning
confidence: 99%